The role of glial cells and apoptosis of enteric neurones in the neuropathology of intractable slow transit constipation. Issue 1 (24th July 2005) - Bassotti, G; Villanacci, V; Maurer, C A; Fisogni, S; Di Fabio, F; Cadei, M; Morelli, A; Panagiotis, T; Cathomas, G; Salerni, B
Abstract : Background: Idiopathic slow transit constipation is one of the most severe and often intractable forms of constipation. As motor abnormalities are thought to play an important pathogenetic role, studies have been performed on the colonic neuroenteric system, which rules the motor aspects of the viscus. Aims: We hypothesised that important neuropathological abnormalities of the large bowel are present, that these are not confined to the interstitial cells of Cajal and ganglion cells, and that the previously described reduction of enteric neurones, if confirmed, might be related to an increase in programmed cell death (apoptosis). Patients and methods: Surgical specimens from 26 severely constipated patients were assessed by conventional and immunohistochemical methods. Specific staining for enteric neurones, glial cells, interstitial cells of Cajal, and fibroblast-like cells associated with the latter were used. In addition, gangliar cell apoptosis was evaluated by means of indirect and direct techniques. Data from patients were compared with those obtained in 10 controls. Results: Severely constipated patients displayed a significant decrease in enteric gangliar cells, glial cells, and interstitial cells of Cajal. Fibroblast-like cells associated with the latter did not differ significantly between patients and controls. Patients had significantly more apoptotic enteric neurones than controls. Conclusion: Severely constipated patients have important neuroenteric abnormalities, not confined to gangliar cells and interstitial cells of Cajal. The reduction of enteric neurones may in part be due to increased apoptotic phenomena.